735. Malaria Chemoprophylaxis Adherence Among U.S. Active Duty Service Members during Deployment to Endemic Regions. (4th December 2021) - Collier, Ryan P; Lindholm, David A; Lalani, Tahaniyat; Telu, Kalyani; Kuo, Huai-Ching; Fraser, Jamie; Ganesan, Anuradha; Kunz, Anjali; Geist, Charla; Yun, Heather; Yun, Heather; Tilley, Drake
Abstract: Background: Military members frequently deploy to malaria-endemic regions. Most cases of travel-related malaria occur due to prophylaxis non-adherence, impacting mission readiness. Factors assessing adherence are described in outbreak settings; we prospectively assess adherence in military travelers. Methods: TravMil is a prospective, observational cohort study of US military beneficiaries traveling outside the US (2010-2019). Our analysis includes only active-duty service members traveling with a military purpose to malaria-endemic regions, who were prescribed malaria prophylaxis, and who completed a pre- and post-deployment survey; they could also enroll after return from deployment. All travelers received pre-travel counseling. Survey responses were assessed using descriptive statistics and multivariate regression to determine risk factors for adherence. Results: 1504 travelers were included (85% male; median age 28 years; 73% white). Median duration of travel was 77 days (12% traveled ≤ 14 days). Africa was the most common destination (33%). Primary prophylaxis included doxycycline (54%) and atovaquone/proguanil (43%). 969 (64%) were fully adherent to their regimen. The frequency of prophylaxis did not match expected values, as 3.6% of subjects reported taking prophylaxis weekly, and 2.9% did not know how often they took it. 103 (6.9%) did not take any of the prescribed regimen. On multivariate analysis, deployers were more likely to adhere if they traveled for ≤ 14 days or to Africa or practiced other mosquito-avoidance behaviors. Study enrollment post-deployment was associated with decreased odds of adherence, as was use of a tent. The use of daily versus weekly prophylaxis was not associated with a difference in adherence, though we had limited subjects prescribed weekly regimens. Figure 1. Reasons for not taking any of the prescribed chemoprophylaxis (n = 103) Table 1. Odds of full adherence to malaria chemoprophylaxis on multivariate logistic analysis Conclusion: Short-duration travel, travel to highly endemic regions, and mosquito-avoidance behaviors were associated with increased adherence to prophylaxis. The lower rate of adherence in post-deployment enrollees may be a surrogate for inadequate counseling or recall bias. Our study highlights potential holes in counseling regarding malaria prophylaxis and the importance of ongoing provider and patient education on malaria. Disclosures: Heather Yun, MD, American Board of Internal Medicine (Individual(s) Involved: Self): Board Member